The Application of Critical Path Method (CPM) Analysis on Traditional Ship Production Process - Hendra Saputra (Politeknik Negeri Batam, 2014)
Most of the traditional ships in Indonesia were built without a special design. Traditional ship design is the result of learning from nature, so there is no planning and calculation of a standard design befor e the ship was built, but the skills acquired by generations of his predecessors. This study is trying to determine the project schedule and the critical path in the traditional shipbuilding by using Critical Path Method. The data for this study was obtained from observing and interview method. Overall analysis found the completion time of a traditional boat building process for the size of 300 gross tonnage require the approximately completion time of 4.4 months. In the production process, there are four critical part which is cannot be delayed the process such as main stiffener/keel assembly, frames assembly, hull assembly and ship launching. Delay work on the point of the critical part will create delays overall production process.